The Economic and Geopolitical Implications of China's Belt and Road Initiative in Eastern Europe: A Case Study on Serbia - Huang, Xin (Transactions on Economics, Business and Management Research, 2024)
This paper critically analyses the economic and geopolitical consequences of China's Belt and Road Initiative (BRI) on Serbia. The primary focus is on the initiative's effects on the country's infrastructure development, employment, and trade sectors. The study adopts a positivist research ethic and employs a deductive technique. It utilizes quantitative methodologies by administering an online survey to 350 practitioners actively engaged in BRI projects in Serbia. The data analysis was conducted using the SPSS program. The research findings demonstrate that the infrastructure investment and employment generation associated with the BRI have had notable positive impacts on Serbia's economic and geopolitical development. Moreover, it has been discovered that trade dynamics with China have the potential to bolster economic growth and foster positive geopolitical relations. Nevertheless, the study admits many limitations, including a restricted sample size and the lack of qualitative data. Future study recommendations encompass the need for enhanced stakeholder engagement on a wider scale and the implementation of longitudinal studies to effectively capture the dynamic and evolving impacts over time.